Pengembangan Model Concept Sentence Learning Berbasis Budaya Multietnis untuk Memfasilitasi Pemahaman Konsep dan Kepedulian Sosial Siswa - Nindy Citroresmi Prihatiningtyas; Rika Wahyuni; Mariyam Mariyam (Didaktik Matematika, 2020)
This study aims to develop a learning model to facilitate students' ability to understand mathematical concepts and character of social care. The developmental research of this study three phases, namely Preliminary research phase development or prototyping phase and assessment phase. The subjects the first trial involved one school and for the second trial involved four junior high schools in Singkawang City which consisted of various ethnicities. In the development stages,a multi-ethnic culture-based concept sentence learning model was produced and learning tools such as lesson plans and worksheets.The instruments used for the feasibility of the model were the validation sheet, the observation sheet, the ability to comprehend the concept, the questionnaire sheet.The results showed that the multiethnic culture-based concept sentence learning model was feasible because it met three criteria:1)valid based on the assessment experts and practitioners,2)practically seen from the results of observations of implementation and student responses to learning and 3)effective in activating students, achieving completeness and fostering the character of student social care.